PERSPEKTIF MAHASISWA DALAM MENINGKATKAN MOTIVASI DAN KUALITAS PEMBELAJARAN PERKULIAHAN ONLINE PRODI MANAJEMEN PENDIDIKAN - Nur, Andi Rasdiana; Sulisyanti, Nur Amaliah; Istiqomah, Istiqomah; Wayong, Muh. (Department of Islamic Education Management, 2026)
The learning process has shifted from face-to-face to online lectures, requiring students and lecturers to maintain their motivation and quality of learning. This study aims to analyze the causes of low student motivation and the quality of lecturers' learning in online lectures in the Islamic Education Management (MPI) Study Program at UIN Alauddin Makassar. The research method used was a qualitative approach with data collection through in-depth interviews. Primary data were obtained from interviews with four MPI students from the classes of 2020, 2022, 2023, and 2025 and two MPI lecturers. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results show that student motivation in online learning tends to be unstable due to limited interaction, technical constraints, and low student active involvement. The quality of online lectures is considered unable to replace the effectiveness of face-to-face learning, especially in terms of the depth of interaction and class control. In conclusion, online learning is more appropriately positioned as a complement to face-to-face learning through a blended learning model. The implications of this research emphasize the importance of strengthening interactive online learning designs, improving lecturer competencies, and supporting institutional policies and infrastructure to improve student motivation and learning quality.